Elementary mathematical analysis with solutions to problems - Yusof Yaacob (Penerbit Universiti Teknologi Malaysia, 2015)
The book covers the topics usually included in an analysis of functions of one real variable: a brief development of real numbers, sequences of real numbers, elementary topology, limits, continuity, differentiation, integration, series of real numbers, power series, sequences of functions and series of functions.